2005
DOI: 10.1063/1.2126112
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doping and thermal stability in HfSiOxNy studied by photoemission and x-ray absorption spectroscopy

Abstract: We have investigated nitrogen-doping effects into HfSiOx films on Si and their thermal stability using synchrotron-radiation photoemission and x-ray absorption spectroscopy. N 1s core-level photoemission and N K-edge absorption spectra have revealed that chemical-bonding states of N-Si3-xOx and interstitial N2-gas-like features are clearly observed in as-grown HfSiOxNy film and they decrease upon ultrahigh vacuum (UHV) annealing due to a thermal instability, which can be related to the device performance. Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…As shown in Table I, nitrogen in dielectrics is very effective in preventing both oxidation and reduction reactions. One possible mechanism is a decrease in the diffusion rates of oxygen atoms 15 and SiO molecules 16 in a HfSiON film that are responsible for oxidation and reduction reactions, respectively ͓Fig. 4͑iii͔͒.…”
mentioning
confidence: 99%
“…As shown in Table I, nitrogen in dielectrics is very effective in preventing both oxidation and reduction reactions. One possible mechanism is a decrease in the diffusion rates of oxygen atoms 15 and SiO molecules 16 in a HfSiON film that are responsible for oxidation and reduction reactions, respectively ͓Fig. 4͑iii͔͒.…”
mentioning
confidence: 99%
“…For sample A, the spectrum comprises two components: the first one at BE = 16.8 eV with a full width at half maximum (FWHM) of 1.16 eV, which is assigned to Hf atoms in stoichiometric HfO 2 , [19] and the second one at 17.4 eV (FWHM = 1.18 eV), which is assigned to Hf atoms in HfSiON. [20] For sample B, three components at lower BE of 15.9 eV (FWHM = 1.17 eV), 16.4 eV (FWHM = 1.17 eV), and 17.3 eV (FWHM = 1.00 eV) are observed, which correspond to Hf atoms in HfN, HfO x N y , and HfSiON, respectively. Therefore, the intermixing of HfO 2 and HfSiON in thinner film and that of HfN, HfO x N y , and HfSiON in a thicker sample caused the peak broadening before RTA.…”
Section: Resultsmentioning
confidence: 94%
“…[6] After RTA, both the thinner and thicker films indicate the dominant component located around 397.8 eV, which corresponds to N atoms bonded with both Si and O. [20] The N concentration decreases in two films and the decrease in the thicker sample is more significant, as shown in Table 1. Since the Hf-N bond is unstable and easily destroyed by RTA treatment, the destruction of Hf-N bonds induces changes in film thickness and composition.…”
Section: Resultsmentioning
confidence: 95%
“…For Y 2 O 3 /Si and HfSiON/Si gate stack structures, it is reported that the interfacial SiO 2 layer depomposition occurs before the high-k material depomposition [11,12].…”
Section: Resultsmentioning
confidence: 99%